1993
DOI: 10.1083/jcb.120.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of glycosylphosphatidylinositol (GPI)-anchored membrane proteins in intact cells: specific amino acid requirements adjacent to the site of cleavage and GPI attachment.

Abstract: Abstract. Mutational studies were previously carried out at the co site in intact cells (Micanovic, R., L. Gerber, J. Berger, K. Kodukula, and S. Udenfriend. 1990. Proc. Natl. Acad. Sci. USA. 87:157-161; Micanovic R., K. Kodukula, L. Gerber, and S. Udenfriend. 1990. Proc. Natl. Acad. Sci. USA: 87:7939-7943) and at the co + 1 and co + 2 sites in a cell-free system (Gerber, L., K. Kodukula, and S. Udenfriend. 1992. J. Biol. Chem. 267:12168-12173) of nascent proteins destined to be processed to a glycosylphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 32 publications
5
85
0
Order By: Relevance
“…We introduced additional prolines, in view of suppressing glypiation. Our results are perfectly consistent with the identification of the natural site as Gly 14 , but we found that it was not possible to suppress completely helix and the site Chimeric constructs are shown at the top. The GPI addition signal is composed of intervening regions (located between the cysteine and the hydrophobic region) and hydrophobic regions from rat (r) or Torpedo (t).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We introduced additional prolines, in view of suppressing glypiation. Our results are perfectly consistent with the identification of the natural site as Gly 14 , but we found that it was not possible to suppress completely helix and the site Chimeric constructs are shown at the top. The GPI addition signal is composed of intervening regions (located between the cysteine and the hydrophobic region) and hydrophobic regions from rat (r) or Torpedo (t).…”
Section: Resultssupporting
confidence: 81%
“…The structural requirements of the C-terminal signal peptides that induce GPI addition have been investigated extensively by the groups of Caras and Udenfriend, by mutagenesis of the "decay-accelerating factor" (9 -12) and of placental alkaline phosphatase (13)(14)(15)(16)(17). They showed that glypiation requires a C-terminal hydrophobic sequence and an upstream cleavage/addition site (2,13).…”
mentioning
confidence: 99%
“…Studies in mammalian cells [5,6] and in Saccharomyces cereisiae [7] have used variants of C-terminal sequences to define the elements that are necessary and sufficient for GPI attachment (reviewed in [8]). In order from the C-terminus, these consist of a stretch of 8-20 hydrophobic residues, a short region of amino acids rich in charged residues and proline, and a domain of three small amino acids, the most N-terminal of which is the attachment or ω site [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have postulated empirical rules to define GPI-attachment signal sequences from a cDNA-sequence. 21 With regard to such a possible signal, peptide Met-983 has not been suggested as a GPIattachment site.…”
Section: Identification Of N-and C-terminal Sequences and Heterogeneitymentioning
confidence: 99%